The polished stone value of local aggregates in Sarawak and its performance on skidding resistance - Latif, Yok (Universiti Malaysia Sarawak (UNIMAS), 2005)
This study program was focused on the quality of aggregates in order to improve the Skid Resistance problem and look their performance in order to support road construction project in Sarawak. Two main types of aggregates has been used namely microtonalite and granite.